Transforming Differences into "Normality". German Unification and the Crisis of the Humanities - Barck, Karlheinz (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1996)
The text, written in spring, 1992, describes certain effects of the German unification process on what has been called the unification of two different scholarly systems. This essay examines how, in the humanities, the hasty political drive to "depoliticize" the scholarly institutions of the former German Democratic Republic and "normalize" them according to Western standards, led to frictions and clashes that run counter to "normalization" as well as to the supposed universality of "Western standards".